Proton therapy for early breast cancer patients in the DBCG proton trial: planning, adaptation, and clinical experience from the first 43 patients. (1st February 2022) - Fuglsang Jensen, Maria; Stick, Line Bjerregaard; Høyer, Morten; Kronborg, Camilla Jensenius Skovhus; Lorenzen, Ebbe Laugaard; Mortensen, Hanna Rahbek; Nyström, Petra Witt; Petersen, Stine Elleberg; Randers, Pia; Thai, Linh My Hoang; Yates, Esben Svitzer; Offersen, Birgitte Vrou
Abstract: Background: The Danish Breast Cancer Group (DBCG) Proton Trial randomizes breast cancer patients selected on high mean heart dose (MHD) or high lung dose (V20Gy/V17Gy) in the photon plan between photon and proton therapy. This study presents the proton plans and adaptation strategy for the first 43 breast cancer patients treated with protons in Denmark. Material and methods: Forty-four proton plans (one patient with bilateral cancer) were included; 2 local and 42 loco-regional including internal mammary nodes (IMN). Nineteen patients had a mastectomy and 25 a lumpectomy. The prescribed dose was either 50 Gy in 25 fractions ( n  = 30) or 40 Gy in 15 fractions ( n  = 14) wherefrom five received simultaneous integrated boost to the tumor bed. Using 2-3 en face proton fields, single-field optimization, robust optimization and a 5 cm range shifter ensured robustness towards breathing motion, setup- and range uncertainties. An anatomical evaluation was performed by evaluating the dose after adding/removing 3 mm and 5 mm tissue to/from the body-outline and used to define treatment tolerances for anatomical changes. Results: The nominal and robust criteria were met for all patients except two. The median MHD was 1.5 Gy (0.5–3.4 Gy, 50 Gy) and 1.1 Gy (0.0–1.5 Gy, 40 Gy). The anatomical evaluations showed how 5 mm shrinkage approximately doubled the MHD while 5 mm swelling reduced target coverage of the IMN below constraints. Ensuring 3–5 mm robustness toward swelling was prioritized but not always achieved by robust optimization alone emphasizing the need for a distal margin. Twenty-eight patients received plan adaptation, eight patients received two, and one received five. Conclusion: This proton planning strategy ensured robust treatment plans within a pre-defined level of acceptable anatomical changes that fulfilled the planning criteria for most of the patients and ensured low MHD.